Instagram and the Strategy of Rudeness: The Phenomenon of Online Bullying Among the Digital Generation from the Perspective of Indonesian Law (International Forum of Researchers and Lecturers, 2025)
This study investigates the phenomenon of online bullying through strategies of rudeness on Instagram, with a particular focus on Indonesia’s digital generation. In the evolving landscape of social media, cyberbullying increasingly manifests through indirect and masked forms of verbal aggression—such as sarcasm, mockery, and humorous insults—that appear socially acceptable but carry harmful intent. The research aims to (1) identify the forms and linguistic strategies of impoliteness employed in digital bullying, and (2) examine the extent to which Indonesian law protects victims of such behavior. Employing a normative juridical method combined with pragmatic linguistic analysis, the study draws upon Jonathan Culpeper’s theory of impoliteness to analyze the communicative tactics used in Instagram interactions. The findings reveal that body shaming, public humiliation, and hate speech are prevalent forms of bullying on the platform, exacerbated by Instagram’s visual and interactive features that facilitate rapid dissemination and public exposure. Although Indonesian legal instruments—such as the Electronic Information and Transactions Law (ITE Law) and the Criminal Code—provide a formal basis for penalizing online bullying, several challenges persist. These include legal ambiguity in defining verbal violence, difficulties in digital evidence collection, and limited public awareness regarding victims’ rights and reporting mechanisms. The study concludes that addressing online bullying requires a multidisciplinary approach that integrates legal enforcement, digital literacy education, and ethical communication practices. Strengthening institutional capacity, promoting awareness campaigns, and refining regulatory frameworks are essential steps toward mitigating the normalization of verbal violence in digital environments. This research contributes to the broader discourse on digital civility and legal reform, offering strategic insights for policymakers, educators, and platform regulators committed to fostering safer online spaces for Indonesia’s youth.